Efektivitas Penambahan Koagulan dan Media Filtrasi dalam Menurunkan Kadar Tss, Amonia dan Fosfat Limbah Cair RSPAU Dr. Suhardi Hardjolukito Yogyakarta - Donni Septiandi; Bambang Suwerda; Adib Suyanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Activities in hospitals not only bring positive impact to general community, but also potential of reduce the quality of environment and public health, e.g. negative effect from the yielded waste. Based on the preliminary study on the liquid waste produced by Air Force Hospital Dr. Suhardi Hardjolukito in Yogyakarta, it was found that the concentration of TSS, ammonia and phosphate were exceeding the quality standard regulated by Yogyakarta Governor’s Decree No 07 in 2010. The aim of the study was to understand the effectiveness of the addition of coagulant consisted of lime and alum, with filtration media of 40 cm-thick quartz sand and 40 cm-thick zeolite in reducing the concentration of the three parameters by conducting a true experiment with pre-test post-test with control group design. The object of this research was the processed liquid waste from the hospital and the subsequent waste water sample were obtained by using composite sampling me-thod. The study was carried out in five replications and taken place at Yogyakarta Polytechnic of Health. Meanwhile, the examination of the parameters were conducted in Health Laboratory Office of Yogyakarta. The data were statistically tested by using one way anova, and the results showed that the coagulants and quartz sand could decrease the concentration of TSS, ammonia and phos-phate as much as 30,91 %, 39,32 % and 36,44%, respectively; while the coagulants and zeolite could lower the concentration of TSS by 46,89 %, ammonia by 68,37 %, and phosphate by 68,38 %). Because the following p-values gained from the statistic test were 0,003; 0,007; and <0,001; respectively, it can be concluded that the coagulant and the filtration media were significantly able for reducing TSS, ammonia and phosphate concentration in the liquid waste, and zeolite was de-termined as the most effective filter.